2017
DOI: 10.3390/ijms18091886
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PALB2 in the DNA Damage Response and Cancer Predisposition

Abstract: The deoxyribonucleic acid (DNA) damage response (DDR) is a major feature in the maintenance of genome integrity and in the suppression of tumorigenesis. PALB2 (Partner and Localizer of Breast Cancer 2 (BRCA2)) plays an important role in maintaining genome integrity through its role in the Fanconi anemia (FA) and homologous recombination (HR) DNA repair pathways. Since its identification as a BRCA2 interacting partner, PALB2 has emerged as a pivotal tumor suppressor protein associated to hereditary cancer susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 154 publications
1
73
0
3
Order By: Relevance
“…So, the mutations in PALB2 normally not only resulted in typical FA phenotypes, but also increased the occurrence of pediatric malignancies, Wilm's tumors, and medulloblastomas (Reid et al, 2007). Importantly, the cancer spectrum caused by mutations in PALB2 is quite similar to that induced by mutations in BRCA2, thereby validating the direct interaction between PALB2 and BRCA2 (Nepomuceno et al, 2017).…”
Section: Palb2/fancnmentioning
confidence: 83%
“…So, the mutations in PALB2 normally not only resulted in typical FA phenotypes, but also increased the occurrence of pediatric malignancies, Wilm's tumors, and medulloblastomas (Reid et al, 2007). Importantly, the cancer spectrum caused by mutations in PALB2 is quite similar to that induced by mutations in BRCA2, thereby validating the direct interaction between PALB2 and BRCA2 (Nepomuceno et al, 2017).…”
Section: Palb2/fancnmentioning
confidence: 83%
“…PALB2 loss-offunction mutations are associated with sensitivity to DNA-damaging agents and poly(ADP-ribose) polymerase 1 inhibitors. 11 To the best of our knowledge, this is the first study to explore PALB2 mRNA expression as a predictive pharmacogenomic marker in NSCLC. We found that PALB2, when highly expressed, is predictive of outcome in response to cisplatin-docetaxel.…”
Section: Discussionmentioning
confidence: 94%
“…PALB2 is located in the 16p chromosome arm and encodes a putative tumor suppressor protein that interacts with BRCA2 through dimerization and the recombinase RAD51. It plays a role in DNA repair by acting in the Fanconi anemia and homologous recombination pathways . PALB2 germline mutations predispose to breast and pancreatic cancers , and its promoter may also be silenced by DNA methylation .…”
Section: Discussionmentioning
confidence: 99%
“…It plays a role in DNA repair by acting in the Fanconi anemia and homologous recombination pathways . PALB2 germline mutations predispose to breast and pancreatic cancers , and its promoter may also be silenced by DNA methylation . PALB2 alterations appear to be rare in glioma with only a single homozygous inactivation of this gene reported among 794 diffuse gliomas in the TCGA dataset (http://www.cbioportal.org).…”
Section: Discussionmentioning
confidence: 99%